THE EFFECT OF PALM FRUIT BUNCHES ASH AND N, P AND K FERTILIZER ON GROWTH AND YIELD OF CELERY IN PEAT SOIL - muji setiawan; maulidi .; putu dupa bandem (Fakultas Pertanian Universitas Tanjungpura, 2020)
Celery plants (Apium graveolens L.) which are cultivated in peat soils face several obstacles such as soil acidity and deficiency of nutrients. Palm fruit bunches ash has an important role to improve pH in soils. Whereas this plants needs N, P and K fertilizers for growth and development. The purpose of this research was to investigate the best interaction between palm fruit bunches ash dosage and N, P and K fertilizer on the growth and yield of celery in peat soils. This research was conducted at the research house of the Faculty of Agriculture, Tanjungpura University, Pontianak, lasted from 16 December 2018 to 14 March 2019. This research used a Factorial Complete Randomized Design method consisting of 2 factors with 3 treatments each, 3 replications and 4 plant samples each treatment. The first factor is the provision of palm fruit bunches ash, called: a1= 4.5 tons/ha, a2 = 6 tons/ha, and a3 = 7.5 tons/ha. The second factor called: p1 = 50% recommended dosage of Urea (75 kg/ha, SP-36 25 kg/ha and KCl 50 kg/ha), p2 = 75% recommended dosage (Urea 112.5 kg/ha, SP-36 37.5 kg/ha and KCl 75 kg/ha), and p3 = 100% recommended dosage, (Urea 150 kg/ha, SP-36 50 kg/ha and KCl 100 kg/ha). The observed variables were root volume (cm3), number of leaf stalks, number of tillers, plant fresh weight (g), and plant dry weight (g). Interaction occurred between oil palm long ash and fertilizer N, P and K on the variable number of tillers, while the variable root volume, number of leaf stalks, fresh weight, and plant dry weight did not occur. Results of this research found an effective of palm fruit bunches ash dosage 4 tons/ha and N, P and K fertilizer with 50% dosage recommended (75 kg/ha, SP-36 25 kg/ha, and KCl 50 kg/ha). Key word : Celery, N, P and K fertilizer, palm fruit bunches ash, peat soil